Assessing the influence of attitudinal function on sustainability awareness in manufacturing industry - Wan Nurul Syahirah, Wan Lanang (2022)
Sustainability as an area of research is growing in importance not only among academicians, but practitioners as well. With the growing demand for environmentally friendly products drive a manufacturer to consider and more concern about green marketing for their company. Accessing a sustainability awareness towards this focal industry is considered as a good target to start the research. Almost 60 to 70 percent of previous research with regard to sustainability awareness is focused more towards subject’s knowledge, never considered a man’s behavior that might be affect the whole result of the awareness. Several academic studies around the world have presenting on how the emotional behavior and awareness can be relate to each other. Thus, this study was undertaken by considering an attitudinal parameter when analyzing the result. Preliminary test or Pilot Run test indicate that most community regardless their background are aware on what is sustainability. By incorporating attitudinal parameter into Green Project Management (GPM) P5 tools, the result of this study suggest that attitude of the person can slightly affect the initial data. Validate by a variable control chart, knowledge and attitude can be formulated as an equal variable to access the awareness. This research study hopes to bring forth the importance of an emotional behavior towards accessing Sustainability Awareness.